Perceived Attributes Towards Development of Muslim Heritage Tourism in the Municipality of Sofronio Española: Basis for Action Plan - Angeles, Ivan P.; Sarail, Judy Ann V. (Future Science / FSH-PH Publications, 2024)
This research explores the potential of Muslim heritage tourism in Sofronio Española, Palawan, as a driver of economic growth and cultural exchange. The study investigates residents' perceived attributes towards this tourism development, focusing on socio-cultural, economic, and environmental aspects. A descriptive correlational design was employed, surveying 381 residents across nine barangays using stratified random sampling. The findings indicate a high level of agreement among residents on the positive socio-cultural impact of preserving Muslim heritage sites, the economic benefits of tourism-related income and job creation, and the necessity of sustainable environmental practices. The demographic profile revealed a predominance of females (61.2%), a youthful population with 60% aged 18-27, and a high level of educational attainment, with 48.6% having attended college. Despite these insights, statistical analysis showed no significant correlation between demographic factors (age, length of residency, educational attainment) and perceived attributes, suggesting widespread support for tourism development across different demographic segments. The study concludes that while demographic factors do not significantly influence perceptions, the overall positive outlook on Muslim heritage tourism highlights its potential for fostering sustainable development. Recommendations include enhancing community engagement, supporting local entrepreneurship, implementing sustainable tourism practices, and developing a comprehensive tourism action plan. These strategies aim to capitalize on the rich cultural and natural assets of Sofronio Española, promoting it as a premier destination for Muslim heritage tourism. This research provides a foundational understanding that can guide policymakers and stakeholders in creating effective tourism development initiatives that benefit both residents and visitors.